1999
DOI: 10.1021/ac981322c
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of Electrogenerated Chemiluminescence by Phenols, Hydroquinones, Catechols, and Benzoquinones

Abstract: Efficient quenching of Ru(bpy)(3)(2+) (bpy = 2,2'-bipyridine) electrogenerated chemiluminescence has been observed in the presence of phenols, catechols, hydroquinones, and benzoquinones. In most instances, quenching is observed with 100-fold excess of quencher over Ru(bpy)(3)(2+), with complete quenching observed between 1000- and 2000-fold excess. The mechanism of quenching is believed to involve energy transfer from the excited-state luminophore to benzoquinone. In the case of phenols, catechols, and hydroq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
138
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(152 citation statements)
references
References 32 publications
11
138
1
2
Order By: Relevance
“…This result may be attributable to generation of compounds such as phenol and catechole that decrease the ECL intensity. 16 On the other hand, for IR28 with the ordinary resistance, the proline content and ECL intensity increased till the 8th and 11th days, respectively (Fig. 4).…”
Section: Resultsmentioning
confidence: 91%
“…This result may be attributable to generation of compounds such as phenol and catechole that decrease the ECL intensity. 16 On the other hand, for IR28 with the ordinary resistance, the proline content and ECL intensity increased till the 8th and 11th days, respectively (Fig. 4).…”
Section: Resultsmentioning
confidence: 91%
“…TCQ belongs to the benzoquinone species, which is well known to be capable of quenching the anodic ECL of Ru(bpy) 3 2+ * via energy transfer. 37 Therefore, the quenching mechanism of PCP on the Ru(bpy) 3 2+ /NGQDs ECL system should be related to the electron transfer between the Ru(bpy) 3 2+ * and TCQ. When PCP and the Ru(bpy) 3 2+ /NGQDs system coexist, the electrons transfer from Ru(bpy) 3 2+ * to TCQ, thus reducing the ECL signal of Ru(bpy) 3…”
Section: +mentioning
confidence: 99%
“…Quenching ECL of the tris(2,2â€Č-bipyridine)ruthenium(II)/ tripropylamine (TPrA) system has been studied quite extensively 10,11 in terms of the mechanism and applications. [4][5][6][7][8][9][10][11][12][13] McCall et al reported on the inhibition of Ru(bpy)3 2+ /TPrA ECL by phenol, substituted phenols, hyroquinones, catechols, and benzoquinones, and suggested a quenching mechanism involving benzoquinone derivatives formed at the electrode surface that quenches ECL via energy transfer.…”
Section: +mentioning
confidence: 99%